Experimental Research of the “Techno-R” Technology in Teaching Foreign - VASSILIEVA, Valentina Nikolaevna; GALEEVA, Gulnara Irekovna; KHROMOVA, Evgeniya Igorevna; LEBLANC, Cеcile (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article provides an overview of modern educational technologies from the perspective of modernizing the traditional education system and the didactic reconstruction of educational material. This article is a detailed description of the experiment, which allows other researchers to repeat and appreciate the "Techno-R" technology. The results of experiential learning were expressed according to the established criteria in digital terms and subjected to mathematical processing according to “Student T-test”. The credibility of the findings made by the authors confirms the amount of the T-criterion in the range of 3.3-6.9, which indicates a high degree of reliability of the results.RESUMEN El artículo proporciona una visión general de las tecnologías educativas modernas desde la perspectiva de la modernización del sistema educativo tradicional y la reconstrucción didáctica del material educativo. Este artículo es una descripción detallada del experimento que permite a otros investigadores repetir y apreciar la tecnología "Techno-R". Los resultados del aprendizaje experimental se expresaron de acuerdo con los criterios establecidos en términos digitales y se sometieron a procesamiento matemático de acuerdo con la "Prueba T de Student". La credibilidad de los hallazgos realizados por los autores confirma la cantidad del criterio T en el rango de 3.3-6.9 que indica un alto grado de confiabilidad de los resultados.